Determination of the drying curves by means of a tray dryer, in the bentonite process activated with H2SO4) at a pilot level - Romero y Otiniano, Pedro (2008)
In the drying process of activated clay there are two important methods that can be used to dry this activated clay: Rotator continuous drying and drying atomization. But to determine the characteristics and mechanism which intervene in the drying of clay is fundamental to use a batch tray drying. The objective of the present work is obtain the curve of drying velocity, fixing sorne initial conditions of humidity, and to define the mechanisms involved in the drying of activated clay with sulphuric acid. Further, this information will be used to scale to continuous drying and find out the equations which govern this process. It was necessary to use a tray of 214 cm2 surface area to charge moist bentonite. Samples were taken containing between 48 and 138 g, and initial humidity between 38 and 50%; to achieve a.final humidity of between about 8 and 13%. Graph of clay total mass (MT) versus drying time (0) show two periods: firstly a linear trend, followed by a no-linear trend. This second period consist of two stages, the first one consist in the formation of a rigid structure ar semi-rigid on the surface of the so/id. The second one consists in the removal of the moisture balance and this is frequently accompanied by an internal vaporization which can cause the so/id expansion. These drying characteristics are presented in graphic N°6 as a curve of drying velocity vs. solid humidity. These second period can be represented by the equation: Wc= 0.003463Xm^1.6556 .